Seeking New Managerial Perspectives for Value Generation - Scaratti, Giuseppe; Ivaldi, Silvia; Frimann, Søren (Academic Quarter | Akademisk kvarter, 2024)
In this article, we take up some of the suggestions presented in the call for papers emphasizing the connections between the concepts of new management and transdisciplinarity. Since the aim of the special issue is to explore experiences and studies related to the development of managerial thought, the innovation in managerial activities, and the overcoming of neoliberal managerial mainstreaming approaches, we solicited contributions connected to ways that management may support the overcomingof critical situations, facing the evolution required to reconfigure existing working, professional, and organizational cultures, and how it may be able to deal with an incoming challenging, paradoxical, and contradictory scenario.